PENGARUH EFIKASI DIRI TERHADAP KREATIFITAS KERJA GURU PEGAWAI NEGERI SIPIL (PNS) SEKOLAH DASAR NEGERI SE-KECAMATAN CIBUNGBULANG - Rahmawati, Ima; Lestari, Hana; Nurhikmah, Handayani (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2022)
Teacher work creativity is the teacher's ability which is manifested by an action in creating new ideas and ideas or modifying existing ideas and ideas into something different and unique with creative and innovative aspects in optimizing all capacities, abilities and skills. The teacher in carrying out his duties as a teacher, such as creating a framework or strategy that fits in realizing a learning plan, provides motivation to students to improve learning achievement, makes the learning atmosphere more enjoyable, and designs interesting, creative and innovative learning media. This study aims to determine the effect of self-efficacy on teacher work creativity. This research was conducted in SDN’s throughout Cibungbulang Bogor District. The number of population in this study was 104 with a sample taken as many as 78 teachers, with probability sampling method with simple random sampling technique. The research method used is quantitative with data collection techniques using a questionnaire. The data analysis technique used is descriptive analysis and simple linear regression analysis. Based on the results of the analysis, it was found that self-efficacy had a significant positive effect on teacher work creativity. This shows that the stronger the effect of self-efficacy, the higher the teacher's work creativity. Therefore, to foster work creativity in teachers, it is expected that they pay more attention to self-efficacy.